Transcriptomic analysis of the larva Taenia multiceps. (December 2017) - Li, W.H.; Zhang, N.Z.; Yue, L.; Yang, Y.; Li, L.; Yan, H.B.; Li, T.T.; Qu, Z.G.; Jia, W.Z.; Fu, B.Q.
Abstract: Taenia multiceps is an adult worm affiliated to Taeniidae family, Platyhelminthes phylum. The larvae of the parasite ( Coenurus cerebralis ) parasitic in the brain and spinal cord in domestic and wild ruminants or humans can led to a fatal central nervous system (CNS) disease. The aims of the present study were to define the transcriptome profiles of the larvae of T. multiceps by RNA-Seq approach, and to generate large functional gene datasets that could be used to predict the key molecular pathways linked to this cestode. Our results generated a total of 39, 094, 890 clean reads that were assembled from the sequence data in 90, 833 contigs. Briefly, 70, 253 unigenes with a mean length of 1492 bp were formed. Based on a sequence similarity search against the databases (NR, Swissport, GO, COG, KEGG) using BLASTX with an E-value cutoff of 10 − 5, 40, 465 of unigenes were identified as coding sequences (CDS) and 3261 were scanned by ESTScan. The present study carried out the transcriptome of the larval stage of T. multiceps, which provides a solid foundation for further studies in molecular biology and biochemistry as well as identification of candidate genes used in diagnosis and vaccine development. Highlights: Cerebral coenurosis is a serious zoonotic parasitic disease in sheep et al. Transcriptomic of the larva Taenia multiceps was first analyzed. The transcriptome described here forms a resource for exploring the biology, pathogenesis, and evolution of T. multiceps .